A escuta como fundamento de processos terapêuticos de sujeitos com afasia: potencialidades da enunciação benvenistiana - Barros, Gabriel Rovadoschi (2025)
This thesis investigates aphasia as an enunciative event that strains the boundaries between body, subject, and discourse. Adopting an interdisciplinary approach—anchored in Émile Benveniste’s theory of enunciation and a clinical mode of listening inspired by psychoanalysis, it proposes to understand aphasia as a site of the subject’s inscription in language, even when language appears fragmented, hesitant, or silent. The theoretical path draws on historical contributions from the field of aphasiology, from Gall and Broca to Wernicke and Freud, recovering Freud’s critique of localizationism and his formulations on the apparatus of language. From there, the thesis articulates Jakobson’s gesture in the linguistic appropriation of aphasias and the shift operated by Benveniste in conceiving language as a condition of subjectivation and listening as an enunciative instance. The empirical material is based on clinical scenes from the Interdisciplinary Group for Coexistence (GIC), in which individuals with aphasia engage in collective speech practices. The analysis of these enunciative scenes reveals that listening - conceived as an ethical and linguistic place - is a condition for the emergence of language and for the subject’s inscription. As outcomes of the research, two articles were produced: the first, an integrative literature review on aphasia and psychoanalytic listening; the second, an enunciative analysis of clinical data, supporting the idea of listening as a function traversed by language and the unconscious. The thesis concludes that clinical listening, rather than repairing failure, sustains the possible word, a gesture that is, at once, ethical, political, and clinical.